2011
DOI: 10.1109/jproc.2011.2158378
|View full text |Cite
|
Sign up to set email alerts
|

Delay- and Disruption-Tolerant Networking (DTN): An Alternative Solution for Future Satellite Networking Applications

Abstract: Satellite communications are characterized by long delays, packet losses, and sometimes intermittent connectivity and link disruptions. The TCP/IP stack is ineffective against these impairments and even dedicated solutions, such as performance enhancing proxies (PEPs), can hardly tackle the most challenging environments, and create compatibility issues with current security protocols. An alternative solution arises from the delayand disruption-tolerant networking (DTN) architecture, which specifies an overlay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(102 citation statements)
references
References 61 publications
1
100
0
1
Order By: Relevance
“…Furthermore, by introducing a sliding window, DTN performance is boosted and eventually the best. The DTN solution have been more recently discussed in Caini et al (2011) which confirms previously observed trends. Furthermore this paper studies DTN security.…”
Section: Some Details On Pepssupporting
confidence: 84%
“…Furthermore, by introducing a sliding window, DTN performance is boosted and eventually the best. The DTN solution have been more recently discussed in Caini et al (2011) which confirms previously observed trends. Furthermore this paper studies DTN security.…”
Section: Some Details On Pepssupporting
confidence: 84%
“…Communication impairments are overcome using replication, parallel forwarding and error correction techniques. DTN as a networking concept and architecture was proposed by the Internet Engineering Task Force (IETF) with pioneering work on the Interplanetary Network (IPN) [3]. DTN has gained popularity over the years with several research in areas such as the Interplanetary Networks (IPNs) for space and satellite communication [3], Airborne Networks (ANs) [4], Delay-Tolerant Sensor Networks [5], Vehicular Ad hoc Networks [6], Underwater Networks (UWNs) [7] and Pocket-Switched Networks (PSNs) [8].…”
Section: Introductionmentioning
confidence: 99%
“…DTN as a networking concept and architecture was proposed by the Internet Engineering Task Force (IETF) with pioneering work on the Interplanetary Network (IPN) [3]. DTN has gained popularity over the years with several research in areas such as the Interplanetary Networks (IPNs) for space and satellite communication [3], Airborne Networks (ANs) [4], Delay-Tolerant Sensor Networks [5], Vehicular Ad hoc Networks [6], Underwater Networks (UWNs) [7] and Pocket-Switched Networks (PSNs) [8]. A number of research works have been carried out and are still on-going in DTN routing [9], congestion control/buffer management [10], convergence layer design [11], application layer design [12], and flow control [13] but very little on DTN security.…”
Section: Introductionmentioning
confidence: 99%
“…Some institutes, specifically, Consultative Committee for Space Data Systems (CCSDS) and Internet Engineering Task Force (IETF) contributes many efforts to create a standard way to solve these problems. As the result of their effort, Delay-and-disruption tolerant networking (DTN) [2] series of protocols are published, intended to become the best solution for communication in space network [3].…”
Section: Introductionmentioning
confidence: 99%